A hydrogeological investigation of the Grootegeluk mine - Johnstone, Andrew Clifford (Rhodes University, Faculty of Science, Department of Geography, 1989)
The study concerns an assessment of the hydrogeological impact of an open cast coal mine in the North Western Transvaal Province of South Africa. The hydrogeological impact of the mine is assessed in terms of groundwater quality and levels. A monitoring system was installed to enable the present and future impact of mining operations on the hydrogeological regime to be assessed. Grootegeluk Mine is situated in the Waterberg Coal Field of South Africa and began production in 1980. The mine extracts fifteen million tons of mine material annually from a single open pit. Forty percent of the mined material is saleable product and the remaining sixty percent is stacked on discard dumps. The Daarby fault forms the northern boundary of the open pit and serves to bring the younger Letaba and Clarens Formations into contact with the older Beaufort and Ecca Groups. The mine discards are deposited north of the fault on a different hydrogeological environment from which they are mined. Dewatering of the mine open pit has resulted in a steady decline in water levels in the Ecca Group, south of the Daarby fault. In contrast, water levels north of the Daarby fault in the Letaba and Clarens Formations have risen. The short term hydrochemical impact of the mine discard dumps and slimes dams have resulted in a rise in the calcium, sulphate, chloride, fluoride and nitrate concentrations of the ambient groundwater . The longer term hydrochemical impact from the waste dumps, acid mine drainage, is not evident at present in the groundwater below the waste dumps. However, it is expected to manifest itself during the next ten years. A monitoring system was installed at the mine to allow groundwater levels and quality to be monitored. By measuring groundwater quality and levels the impact of the mine on the regional hydrogeology can be monitored and assessed presently, and during the next forty years of production. Monitoring will also enable the timeous implementation of remedial measures at an early stage and eliminate the need for large late stage "clean up" operations. Future monitoring of both water levels and quality will be crucial in evaluating the mine's impact on the regional groundwater regimes over the next forty years of production. The remedial measures recommended for leachate presently emanating from the waste dumps and slimes dams north of the Daarby fault, are a number of collector wells drilled into the basalts and sandstone north of the Daarby fault. The proposed positions of the wells (boreholes) are as close as possible to the dumps and slimes dams with expansion taken into consideration. The boreholes should be designed to lower the water level in the vicinity of the dumps in order to create a nett groundwater gradient towards the dumps and as a result, halt the spread of leachate away from the dumps. Grootegeluk plans to backfill the open pit with plant discards on completion of the mining of zone 2. The backfilled material will consist of the currently produced plant waste and will be covered with overburden and topsoil. It is expected that the backfilling will have a major impact on groundwater quantity if no remedial measures are implemented. The two remedial measures discussed are chemical treatment of the discard material before backfilling or the continual abstraction of water from the pit resulting in a nett groundwater inflow into the pit. No material from the present waste dumps and slimes dams will be transported into the open pit as backfill material
Keywords: Hydrogeology -- South Africa; Coal mines and mining -- South Africa